ANALISIS IMPLEMENTASI PERENCANAAN PAJAK SEBAGAI UPAYA PENINGKATAN KINERJA PERUSAHAAN PADA PT. PERKEBUNAN NUSANTARA II BULU CINA - Windy Hasanah; Ratih Anggraini Siregar (Jurnal Widya, 2024)
Tax planning is a strategies for managing company finances to minimize tax obligations in ways that do not violate tax regulations. This research aims to determine the ongoing implementation of tax planning as an effort to improve company performance at PT. Perkebunan Nusantara II Bulu Cina. This research uses a qualitative method with a descriptive analysis approach with data collection techniques through interviews and supporting documents, and processed using the Nvivo 12 pro application. The results of this research conducted show that PT. Perkebunan Nusantara II Bulu Cina has not fully implemented its tax planning even though it has done it correctly according to the law. The advice I give in this research is PT. Perkebunan Nusantara II Bulu Cina can add food costs and transportation costs to become positive correction fiscal costs in the implementation of tax planning so that it can reduce the company's Income Tax payments owed.